Case report: Thoracolumbar spinal stenosis associated with alkaptonuria - Ding, Hong; Wang, Liang; Feng, Gan-Jun; Song, Yue-Ming; Liu, Li-Min (Frontiers in Surgery, 2023)
Background Alkaptonuria is a rare autosomal genetic disorder with an incidence of about 1 in 1 million per year. Spinal involvement often manifests in the later stages of the disease. However, this is the first report of the presentation of thoracolumbar spinal stenosis. Case presentation We report the case of a 61-year-old female patient with significant thoracolumbar stenosis symptoms. The patient had obvious kyphosis with preoperative lower extremity muscle strength grade 2/5. Symptoms and imaging signs initially suggested ankylosing spondylitis. This patient was classified into motor incomplete injury (ASIA C). However, the patient was found to have melanin deposits on the sclera and skin, and the urine was darkened at rest. CT and MRI both suggested no bone bridge connection between vertebrae, which was the key difference between ankylosing spondylitis and alkaptonuria in imaging. Most importantly, urine specimen testing and intraoperative pathology demonstrated alkaptonuria. The patient underwent spinal decompression and vertebral body fixation. Postoperative recovery was good: the patient had significantly relieved pain and could stand and walk. Conclusion This case is the first report of thoracolumbar spinal stenosis associated with alkaptonuria involving the spine.